DEVELOPMENT OF MRV FUNCTION MODE FOR PRACTICAL LEARNING IN REFRIGERATION AND AIR CONDITIONING SYSTEM - Mutaufiq, Mutaufiq; Irwanto, Asep A. R.; Taqwali Berman, Ega Taqwali Berman; Sumardi, Kamin (Journal of Mechanical Engineering Education, 2025)
Recovery and Vacuum Machine (MRV) is a refrigerant recovery tool in practical courses, so that refrigerant is not wasted during practicum. MRV is important to develop in order to improve practicum services. This study aims to develop MRV so that it can carry out the refrigerant recycle-recovery and recharging processes practically. MRV development is carried out experimentally through a research and development approach. The MRV trial results were carried out on a refrigerator type cooling machine. Testing to determine the performance of the MRV when working on vacuum, recovery-recycle, and refrigerant recharge modes automatically and to determine the performance of the refrigerator after recovery-recycle. The results of the development in the form of a new MRV construction with dimensions of 55 cm x 49 cm x 55.5 cm have been realized. MRV testing shows that the MRV results can work on vacuum, recovery-recycle and refrigerant recharging modes well at a Vacuum time setting of 10 minutes, recovery-recycle 5 minutes, and recharging 5 minutes. In addition, the refrigerator performance observed through the parameters of evaporator cabin temperature, electrical power, and compressor pressure showed good results.